Combination of Clostridium butyricum and Corn Bran Optimized Intestinal Microbial Fermentation Using a Weaned Pig Model - Zhang, Jie; Sun, Jian; Chen, Xiyue; Nie, Cunxi; Zhao, Jinbiao; Guan, Wenyi; Lei, Lihui; He, Ting; Chen, Yiqiang; Johnston, Lee J.; Zhao, Jinshan; Ma, Xi (Frontiers in Microbiology, 2018)
Experimental manipulation of the intestinal microbiota influences health of the host and is a common application for synbiotics. Here Clostridium butyricum (C. butyricum, C.B) combined with corn bran (C.B + Bran) was taken as the synbiotics application in a waned pig model to investigate its regulation of intestinal health over 28 days postweaning. Growth performance, fecal short chain fatty acids (SCFAs) and bacterial community were evaluated at d 14 and d 28 of the trial. Although the C.B + Bran treatment has no significant effects on growth performance (P > 0.05), it optimized the composition of intestinal bacteria, mainly represented by increased acetate-producing bacteria and decreased pathogens. Microbial fermentation in the intestine showed a shift from low acetate and isovalerate production on d 14 to enhanced acetate production on d 28 in the C.B + Bran treatment. Thus, C.B and corn bran promoted intestinal microbial fermentation and optimized the microbial community for pigs at an early age. These findings provide perspectives on the advantages of synbiotics as a new approach fir affective utilization of corn barn.